2020
DOI: 10.1038/s41598-020-60362-2
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum cultivation affect microbial community structure of soil, wood segments and tree roots

Abstract: The popular medicinal mushroom Ganoderma lucidum (Fr.) Karst. [Ling Zhi] has been widely used for the general promotion of health and longevity in Asian countries. Continuous cultivation may affect soil microbe and soil properties. However, the effect of G. lucidum cultivation on related wood segments, soil and tree roots microbial communities and soil properties is remain unknown. In our study, the microbial communities of soils, wood segments, and tree roots before and after G. lucidum cultivation were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The bacterial V3-V4 region of 16S rRNA gene was amplified with the primers 338F (ACTCCTACGGGAGGCAGCA) and 806R (GGACTACHVGGGTWTCTAAT) (Ren et al, 2020). ITS1F (CTTGGTCATTTAGAGGAAGTAA) and ITS2R (GCTGCGTTCTTCATC GATGC) were used to amplify fungal ITS1 region (Costa et al, 2021;White et al 1990).…”
Section: Dna Extraction Rdna Amplification and Sequencing Analysismentioning
confidence: 99%
“…The bacterial V3-V4 region of 16S rRNA gene was amplified with the primers 338F (ACTCCTACGGGAGGCAGCA) and 806R (GGACTACHVGGGTWTCTAAT) (Ren et al, 2020). ITS1F (CTTGGTCATTTAGAGGAAGTAA) and ITS2R (GCTGCGTTCTTCATC GATGC) were used to amplify fungal ITS1 region (Costa et al, 2021;White et al 1990).…”
Section: Dna Extraction Rdna Amplification and Sequencing Analysismentioning
confidence: 99%
“…Fungi were possibly impacted by the presence of TOC and trace metal elements in fertilizer. It was reported that bacterial metabolism altered nitrogen-phosphorus synergy while percentage of fungi increase with higher of organic carbon content [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, alpha diversity indices of bacterial community decreased after the cultivation of O. raphanipes, which may be due to the consumption of soil nutrient and the increase of secondary metabolites produced by fruiting bodies. The decrease of bacterial community diversity in casing soil is recognized as an important factor for the occurrence of continuous cropping obstacle of edible fungi (Ke et al 2019;Ren et al 2020) or other crops (Wang et al 2019). Therefore, it is very important to maintain high diversity coupling with functional redundancy of bacterial community for the healthy growth and high yield of edible fungi and other crops.…”
Section: Discussionmentioning
confidence: 99%